Recovery from posttraumatic stress symptoms: a qualitative study of attributions in survivors of war - Ajduković, Dean; Ajduković, Dea; Bogić, Marija; Frančišković, Tanja; Galeazzi, Gian Maria; Kučukalić, Abdulah; Lečić-Toševski, Dušica; Schützwoh, Matthias; Priebe, Stefan (2013)
Objective: The study explored factors to which people traumatized by war attribute their recovery from posttraumatic symptoms. Method: In-depth interviews were conducted with two groups of participants with mental sequelae of the war in the former Yugoslavia: 26 people who had recovered from posttraumatic stress disorder (PTSD) and 17 people with ongoing symptoms of PTSD. Participants could attribute their recovery to any event, person or process in their life that they felt contributed to their healing. The material was subjected to thematic analysis. Results: Participants attributed their recovery to eight themes. Six of them described healing factors for both groups of participants: social attachment and support, various strategies of coping with symptoms, hardiness personality, mental health treatment, received material support, and normalization of everyday life. In addition to the common factors, recovered participants reported community involvement as healing, and recovered refugees also identified feeling safe after resolving their civil status as helpful. Unique to there covered group was that they had reciprocal relations in social attachment and support, maintained future oriented coping and emphasised their resilient personality style. Conclusions: The reported factors of recovery are consistent with sets of protective factors in models of mental health protection, models of resilience and recommended interventions in the aftermath of massive trauma. The findings from the present study can inform psychosocial interventions to facilitate recovery from posttraumatic symptoms of people affected by war and upheaval.
European Comission
ENG